2014
DOI: 10.4082/kjfm.2014.35.4.190
|View full text |Cite
|
Sign up to set email alerts
|

Association between Nutrition Label Reading and Nutrient Intake in Korean Adults: Korea National Health and Nutritional Examination Survey, 2007-2009 (KNHANES IV)

Abstract: BackgroundNutrition labels provide various information on the nutrient contents of food. However, despite the recent increase in the interest in dietary intake and expansion of related policies, studies on the association between nutrition label reading and dietary intake are lacking in Korea.MethodsThis study analyzed the 2007-2009 KNHANES (Korean National Health and Nutrition Examination Survey) data. To examine macronutrients and micronutrients intake according to nutrition label reading, analysis of covari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 21 publications
3
21
0
Order By: Relevance
“…The sample for KNHANES was selected using a stratified, multistage, cluster-sampling design with proportional allocations based on the National Census Registry. The 2007The , 2008The , 2009The , 2010, and 2012 KNHANES database comprised data of 4,594,9,744,10,533,8,958,8,518, and 8,058 individuals, respectively, out of a total of 550,405 participants. Individuals who participated in the nutritional survey were considered (n ¼ 45,031).…”
Section: Methodsmentioning
confidence: 99%
“…The sample for KNHANES was selected using a stratified, multistage, cluster-sampling design with proportional allocations based on the National Census Registry. The 2007The , 2008The , 2009The , 2010, and 2012 KNHANES database comprised data of 4,594,9,744,10,533,8,958,8,518, and 8,058 individuals, respectively, out of a total of 550,405 participants. Individuals who participated in the nutritional survey were considered (n ¼ 45,031).…”
Section: Methodsmentioning
confidence: 99%
“…Studies also show a positive effect of health status on the search for nutrition information (Kim et al, 2001;Lin et al, 2004). Empirical evidence also shows that people with chronic diseases such as hypertension, diabetes and dyslipidemia are more likely to be non-users of nutritional information as shown in a Korean study by Kim et al (2014).…”
Section: Literature Reviewmentioning
confidence: 95%
“…demographic variables, includes gender, age and ethnicity. Past studies found that females seem to be more likely to use nutrition labels compared to males (Guthrie et al, 1995;Mannell et al, 2006;Kim et al, 2014;Cheah et al, 2015). For females, nutritional information is used to make food choices as they are more interested and concerned about their physical image, diet and health (Cheah & Yip, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations